Penerapan Pendekatan Kontekstual dalam Pembelajaran Bahasa Indonesia di RAM Sapugarut Buaran Kab Pekalongan Jawa Tengah - Hartatik , Retno; Rahmawati, Rahmawati; Rahmayanti, Rahmayanti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the implementation of the contextual approach in Indonesian language learning at RAM Sapugarut, Buaran, Pekalongan Regency, Central Java. The research employs Classroom Action Research (CAR) using the Kemmis and McTaggart model, which includes planning, action, observation, and reflection in two cycles. The subjects are fifth-grade students who face difficulties in understanding Indonesian language material through conventional methods. Data were collected through observations, interviews, learning outcome tests, and documentation. The findings indicate that applying the contextual approach significantly improves students' comprehension and language skills. In the first cycle, learning outcomes increased by 18%, and in the second cycle, they improved by 35%. This approach enables students to relate the material to real-life experiences, making learning more meaningful and engaging. The study concludes that the contextual approach is effective in enhancing the quality of Indonesian language learning at the elementary school level.